Estimating the role of single-nucleotide polymorphism (rs1800629)-308 G/A of TNF-alpha gene as genetic marker associated with angina pectoris in a sample of Iraqi patients - Shaimaa Y. Abdulfattah; Farah Thamer Samawi (Journal of Genetic Engineering and Biotechnology, 2023)
Abstract Background Angina pectoris (AP) occurs when oxygen and other nutrients are insufficient to meet the metabolic needs of the heart muscle. Stable angina is the most common, while the unstable angina is less frequent. Tumor necrosis factor alpha (TNF-alpha) is a pleiotropic cytokine plays a vital function in the immune response regulation. TNF gene cluster contains many polymorphisms; the most commonly investigated polymorphism is the rs1800629 SNP. This SNP, located at − 308 position with regard to the TNF promoter region, replaces guanine (G) with adenine (A), with the allelic types − 308 G/A, and has been linked to a variety of inflammatory condition and autoimmune diseases. The − 308 G/A SNP was investigated in AP and interconnected to the TNF level to figure out the responsibilities of TNF-alpha gene polymorphism in the pathogenesis of AP. Method The current work design as a case–control study that involves 300 participant divided to 200 patients evaluated as (stable angina n = 100 and unstable angina n = 100) compared with 100 apparently healthy control subjects. The serum level of TNF-alpha was assessed via enzyme-linked immunosorbent assay (ELISA)/sandwich method. The genotype and allele frequency distribution of TNF-alpha rs1800629 gene polymorphism were investigated by TaqMan probe of allelic discrimination method. Results The levels of TNF-alpha were significantly higher in patients with stable and unstable angina pectoris in comparison with controls. The deviation from Hardy–Weinberg equilibrium (HWE) of TNF-alpha genotypes was obvious in control and unstable angina pectoris groups. Moreover, the significant differences between patients with AP and controls under the five genetic models consider the association between TNF-alpha (rs1800629) − 308 G/A and AP with OR > 1. However, data analysis of allelic and genotypic of (rs1800629) − 308 G/A revealed higher significantly differences of GG homozygous and GA heterozygous proportions between stable angina patients and control. The A allele was more represented as etiological allele, and G allele was represented as protective allele. The serum levels of TNF-alpha were significantly higher in subjects with genetically mutated AA genotypes than in subjects with wild GG genotypes in the study groups. ROC curve analysis found the best cutoff value of TNF-alpha level was 77.25 pg/ml. Conclusion As the results, our data observed a linked of TNF-alpha (rs1800629) − 308 G/A genetic variant with angina pectoris patients, and the A allele has been linked to the production or expression of TNF-alpha serum level and represented an etiological factor of angina pectoris.